1992
DOI: 10.1128/jb.174.13.4457-4462.1992
|View full text |Cite
|
Sign up to set email alerts
|

Replication of prophage P1 is cell-cycle specific

Abstract: P1 prophage replication during the Escherichia coli division cycle has been analyzed by using the membrane-elution technique to produce cells labelled at different times during the division cycle and scintillation counting for quantitative analysis of radioactive prophage DNA. P1 prophage replicates during a restricted portion of the bacterial division cycle, like the minichromosome, but at a time during the division cycle different than the time at which the minichromosome replicates in the same cell. A high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Consistent copy number in all cells of a culture can be achieved by timing the replication of the plasmid with the cell cycle, to ensure that the copy number has doubled before division (20)(21)(22)(23)(24), and by evenly partitioning plasmids into future daughter cells preceding division (25). Only the low-copy-number plasmids of E. coli (and, of course, the chromosome) have replication timed with the cell cycle (20)(21)(22)(23)(24).…”
Section: All-or-none Induction or Expressionmentioning
confidence: 99%
“…Consistent copy number in all cells of a culture can be achieved by timing the replication of the plasmid with the cell cycle, to ensure that the copy number has doubled before division (20)(21)(22)(23)(24), and by evenly partitioning plasmids into future daughter cells preceding division (25). Only the low-copy-number plasmids of E. coli (and, of course, the chromosome) have replication timed with the cell cycle (20)(21)(22)(23)(24).…”
Section: All-or-none Induction or Expressionmentioning
confidence: 99%
“…Keasling et al [2,11] proposed that the F plasmid and P1 prophage replicated when the mass per plasmid origin reached a critical value (the initiation mass). This mechanism would be analogous to that proposed for the chromosomal origin [8,12].…”
Section: Model For the Timing Of Plasmid Replicationmentioning
confidence: 99%
“…Recently, we showed that the low-copy F plasmid and P1 prophage replicate in a cell-cycle-specific manner and that replication occurs when a constant mass per origin is achieved (4,5). In contrast, the high-copy ColEl-type plasmids replicate in a cell-cycle-independent manner (9,14).…”
mentioning
confidence: 99%
“…In light of the similarities in structure and function of the R6K plasmid and the low-copy F and P1 plasmids (large, conjugative, multiple origins of replication, DNA polymerase I independent), one might have expected the R6K plasmid to replicate in a cell-cycle-specific manner like these low-copy plasmids (4,5). However, if one considers the very high copy number of Replication of the mini-R6K plasmid pMF26 and the minichromosome pAL49 during the E. coli division cycle.…”
mentioning
confidence: 99%